2008
DOI: 10.1097/mlg.0b013e31815ae3d2
|View full text |Cite
|
Sign up to set email alerts
|

Patient Compliance to Radiation for Advanced Head and Neck Cancer at a Tertiary Care County Hospital

Abstract: Compared with other institutions, HNSCC patients in this setting are less likely to complete a prescribed therapeutic regimen. Patient and tumor characteristics measured in this study do not predict compliance. Organ preservation protocols require further evaluation in populations where compliance is suspect. Future research must examine interventions to improve compliance and assessment of its impact on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…Cancer patients treated by the Head and Neck service at CCH represent a different population than is seen nationally in that they are younger, unemployed, derive from minority populations, and have relatively advanced Editor stage disease at presentation. 3 A previous study examining this patient population showed that compliance to radiation therapy was poor. This group had frequent deviation from prescribed radiation treatment plans resulting in treatment interruption and prolongation.…”
Section: Introductionmentioning
confidence: 97%
“…Cancer patients treated by the Head and Neck service at CCH represent a different population than is seen nationally in that they are younger, unemployed, derive from minority populations, and have relatively advanced Editor stage disease at presentation. 3 A previous study examining this patient population showed that compliance to radiation therapy was poor. This group had frequent deviation from prescribed radiation treatment plans resulting in treatment interruption and prolongation.…”
Section: Introductionmentioning
confidence: 97%
“…In head and neck and cervical cancer, treatment interruptions for radiation or chemoradiotherapy are noted in 35-55% of the patients (Serkies and Jassem, 2004;Patel et al, 2008;Fesinmeyer et al, 2009;Sethi et al, 2010). At one Chicago county hospital, 40% of the patients planned for chemo-radiotherapy did not receive the treatment course (Patel et al, 2008). Patients who do not receive CDT after diagnosis need to be identified since it adversely impacts the national resources.…”
Section: Discussionmentioning
confidence: 99%
“…Patel and colleagues, evaluated the predictive value of ethnicity, gender, primary tumor site, stage and nodal status, but did not find any significant variable that could predict for noncompliance. [5] Rajni A. Sethi and colleagues, evaluated several demographic, toxicity and treatment variables for reasons for missed treatment, they found patients with percutaneous endoscopic gastrostomy tube were more likely to missed treatment (P=.01). No other variable showed a significant association with missed treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have evaluated loss of local control with increased length of treatment time for various head and neck patients, with a calculated mean reduction in 5 years local control of 1.7% (range 0.4% to 2.9%) for each day that treatment is prolonged. [5] In this study, we document compliance rates, common reasons, why treatments are missed and evaluate whether demographic, tumor related and treatment related factors are correlated with treatment compliance in head and neck cancer patients from the institution.…”
Section: Introductionmentioning
confidence: 99%